Effective decontamination and subsequent plantlet regeneration of sugarcane (Saccharum officinarum L.) in vitro - Danso, K.E.; Azu, E.; Elegba, W.; Asumeng, A.; Amoatey, H.M.; Klu, G.Y.P. (International Journal of Integrative Biology, 2011)
An effective sterilisation regime and protocol for subsequent plantlet regeneration from bud explants was developed for sugarcane cultivars, Ragna, Natal Coimbatore 339 (NCo339) and local sugarcane cultivar (LSC). Double sterilisation with 0.2 and 0.1% mercuric chloride for 15 minutes and 5 minutes respectively resulted in 90% decontamination frequency. However, post sterilisation survival on MS medium amended with 30g/l sucrose, 5mg/l BAP, 2mg/l IAA, 2mg/l GA3 and 3g/l activated charcoal required the incorporation of 200μg/ml amphotericin B and 100μg/ml cefotaxime indicating that the contaminants were endophytic. The culture of double sterilised bud explants of local sugarcane cultivar, Ragna and NCo 339 in the presence of the antibiotics resulted in single or multiple shoot development. These shoots developed roots on MS medium supplemented with 5mg/l NAA. Additionally, in vitro conserved plantlets used as explants also developed multiple shoots. Post-flask acclimatization was independent of age of plantlets. The protocol for effective sterilisation and subsequent successful regeneration of plantlets from bud explants once standardized can be utilized for rapid multiplication and dissemination of newly-released varieties and disease-free stock for farmers. © IJIB, All rights reserved.
Keywords: Amphotericin; Cefotaxime; Decontamination frequency; Double sterilization